SCABIOSIS IN A 1-YEAR OLD DOMESTIC CAT ACCOMPANIED BY LEUKOCYTOSIS AND NORMOCYTIC NORMOCHROMIC ANEMIA - I Gede Bagas Upaditha Adresya Kaler; Sri Kayati Widyastuti; I Putu Gede Yudhi Arjentinia (Fakultas Kedokteran Hewan Universitas Udayana, 2024)
Scabiosis is a zoonotic skin disease of cats caused by the Notoedres cati mite. The purpose of this article is to provide information about the causes and effects of scabiosis infection caused by Notoedres cati mites and its treatment. Kuni cat had clinical symptoms of itching or pruritus for one month. Clinical examination found lesions such as hyperkeratosis, alopecia accompanied by erythema, ulcers, and crusts on the head, ears, neck, front legs, and tail. The results of the supporting examination using the superficial skin scraping method found the presence of Notoedres cati. Hematological examination results showed an increase in white blood cell count (leukocytosis) and a decrease in red blood cells resulting in anemia. Based on anamnesis, clinical examination, and supporting examination, the case cat was diagnosed with scabiosis accompanied by leukocytosis and normochromic normocytic anemia. The case cat was given causative therapy in the form of ivermectin as much as 0.04 mL subcutaneously with two administrations in a 14-day interval. Symptomatic therapy was given diphenhydramine HCI subcutaneously as much as 0.16 mL with two administrations in 14-day intervals and Chlorpheniramine maleate as much as ½ tablet every 12 hours, for 14 days orally. Supportive therapy given is fish oil soft gel once a day orally for 14 days. In addition, topically by bathing the cat twice a week using sulfur soap and blood enhancer sangobion capsules once a day orally for 14 days. After treatment for two weeks the case cat experienced healing characterized by the disappearance of pruritus and lesions such as hyperkeratosis, alopecia accompanied by erythema, and ulcers. Things that must be considered in preventing scabiosis infection in cats are not releasing cats and keeping cats clean by bathing cats twice a month.